Reinforcing Adherence to Antihypertensive Medications. Issue 1 (21st November 2014) - Petry, Nancy M.; Alessi, Sheila M.; Byrne, Shannon; White, William B.
<x xml:space="preserve">Abstract</x> This pilot study evaluated a reinforcement intervention to improve adherence to antihypertensive therapy. Twenty‐nine participants were randomized to standard care or standard care plus financial reinforcement for 12 weeks. Participants in the reinforcement group received a cell phone to self‐record videos of adherence, for which they earned rewards. These participants sent videos demonstrating on‐time adherence 97.8% of the time. Pill count adherence differed significantly between the groups during treatment, with 98.8%±1.5% of pills taken during treatment in the reinforcement condition vs 92.6%±9.2% in standard care (P<.002). Benefits persisted throughout a 3‐month follow‐up, with 93.8%±9.3% vs 78.0%±18.5% of pills taken (P<.001). Pill counts correlated significantly (P<.001) with self‐reports of adherence, which also differed between groups over time (P<.01). Systolic blood pressure decreased modestly over time in participants overall (P<.01) but without significant time‐by‐group effects. These results suggest that reinforcing medication adherence via cellular phone technology and financial reinforcement holds potential to improve adherence.